Plant Density and Nitrogen Supply Affect the Grain-Filling Parameters of Maize Kernels Located in Different Ear Positions - Wei, Shanshan; Wang, Xiangyu; Li, Guanghao; Qin, Yingying; Jiang, Dong; Dong, Shuting (Frontiers in Plant Science, 2019)
Although yield outputs of maize (Zea mays L.) have improved markedly over the last century, procedures for improving the grain-filling process remain elusive. Our aim in this study was to relate grain-filling variations in maize (including kernels in apical and medium positions in the ears) to plant density and nitrogen (N) application rate using a crossed experimental design. We also investigated changes in zeatin riboside (ZR), indole-3-acetic acid (IAA), abscisic acid (ABA) and gibberellins (GAs) in the kernels during the grain-filling period. Two high-yield maize varieties cultivated extensively in China were field grown under normal (67,500 pl ha–1) and high (97,500 pl ha–1) densities, and supplied with low, normal and high (0, 180 and 360 kg N ha–1) concentrations of N. Kernel weight (KW), the maximum grain-filling rate (Gmax), the average grain-filling rate (Gave), and the kernel weight increment achieving Gmax (Wmax) were all significantly depressed under high density (HD) conditions, but increased N supply partially offset the losses. Variations in ZR, IAA and ABA contents tracked the variations in KW, but variations in GAs contents did not. Correlation analysis indicated that plant density and N rate affected KW mainly by influencing the grain-filling rate. Furthermore, the grain-filling parameters (closely related to TKW) had strong canonical correlations with the contents of all hormones across the whole filling period; ZR content had the strongest relationships with the grain-filling parameters. In comparison with kernels located in the middle ear position, apical kernels had lower grain-filling rates, Wmax values, and ZR, IAA, and ABA contents, but higher GAs contents through the whole filling period. Apical kernels were more sensitive to N application rate than middle position kernels, especially under HD conditions. In conclusion, increasing the N application rate may be an effective procedure for improving the grain-filling rate and KW of maize plants grown at HD.